A Theory of Workers' Remittances with An Application to Morocco - Bouhga-Hagbe, Jacques (IMF Working Papers; Working Paper, 2004)
This paper provides a model on how altruism, "attachment" to the home country, and portfolio diversification may act as potential motives behind workers' remittances. It shows that the level of workers' remittances depends on how great are their degrees of altruism and "attachment" to their home country, and should also depend on interest rate differentials between the home country and the country of residence if portfolio diversification motives are significant in the decision to remit. The model is applied to Morocco using co-integration techniques. The paper then discusses the stability of remittances in Morocco and the policy implications in light of the empirical findings.